Analisis Environmental, Social, dan Governance (ESG) Terhadap Nilai Perusahaan Pada PT Antam Tbk. - Febriyanti Artika Putri; Ida Bagus Ketut Bayangkara (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the implementation of Environmental, Social, and Governance (ESG) principles by PT Aneka Tambang Tbk (ANTAM) and their impact on the company's value. The research is motivated by the growing demand for businesses to operate in a sustainable and responsible manner. A qualitative descriptive method was employed, using secondary data from sustainability reports, official publications, and relevant articles. The findings indicate that ANTAM actively applies ESG principles through the formation of a dedicated ESG team, transparent reporting, and comprehensive risk management. A concrete example is the PEPELING Cisangku program, which integrates environmental conservation with community empowerment. The effective implementation of ESG has strengthened investor trust, as reflected in ANTAM’s significant net profit and state contributions in 2023. The implications of this study underscore the importance of ESG integration as a long-term strategy to enhance competitiveness and generate sustainable value for stakeholders.